Ilgųjų ir trumpųjų balsių priešpriešos nykimas miestiečių lietuvių kalboje - Grumadienė, Laima (Baltistica, 1989)
THE DISAPPEARANCE OF OPPOSITION BETWEEN LONG AND SHORT VOWELS IN URBAN LITHUANIANThe spoken Lithuanian in Vilnius was studied, special attention being paid to the contacts of languages and the mixture of dialects. Over 70 informants were examined and their speech was thoroughly investigated using a complex of methods and techniques. The existence of some sociolinguistic variances systematically appearing and their close connection with subjective evaluation have been established.It might be concluded from the data obtained that the main linguistic characteristics of Lithuanian spoken in Vilnius are similar to those known in the Lithuanian dialects.